Healthcare utilization and costs among relapsed or refractory multiple myeloma patients on carfilzomib or pomalidomide as monotherapy or in combination with dexamethasone. (3rd August 2019) - Hagiwara, May; Panjabi, Sumeet; Sharma, Arati; Delea, Thomas E.
Abstract: Aim: To compare monthly healthcare resource utilization (HRU) and costs among adult patients with multiple myeloma (MM) receiving second or subsequent line of treatment (LOT) with carfilzomib or pomalidomide as monotherapy or in combination with dexamethasone. Methods and materials: Adult MM patients who received carfilzomib or pomalidomide as second/subsequent LOT between 2006 and 2014 were selected from the MarketScan databases. LOT was determined using Medical/pharmacy claims using a published algorithm. For each patient, first LOT with carfilzomib or pomalidomide was defined as index LOT. Patients with first LOT as index LOT, who received other chemotherapy in combination with carfilzomib or pomalidomide, or who underwent stem cell transplant (STC) during index LOT were excluded. Monthly HRU and costs during index LOT were compared using inverse probability of treatment weights (IPTW) based on propensity scores for receipt of carfilzomib estimated by logistic regression with LOT, patient demographics, Charlson index, comorbidities, pre-index healthcare cost, and receipt of prior SCT as covariates. Results: After weighting, baseline characteristics were well balanced among 114 carfilzomib and 144 pomalidomide patients. Mean (95% CI) numbers of outpatient visits per month were 7.1 (5.2–8.0) with carfilzomib and 4.7 (3.9–6.1) with pomalidomide ( p = 0.006). Otherwise, there were no statistically significant differences between the groups in mean monthly HRU and costs or median time to therapy discontinuation. Mean (95% CI) monthly total healthcare costs were 19, 776 (15, 322–27, 748) with pomalidomide and 17, 321 (12, 412–21, 874) with carfilzomib ( p = 0.522). Limitations: Comparison of carfilzomib vs pomalidomide may be biased if there are unobserved factors not balanced by IPTW. The relatively small sample size limits the power of analyses to detect potential differences between treatment groups. Conclusions: Monthly HRU and costs are similar among patients with relapse or refractory MM patients receiving carfilzomib or pomalidomide as monotherapy or in combination with dexamethasone.